Children seen frequently out of hours in one general practice. Issue 6810 (2nd November 1991) - Morrison, J M; Gilmour, H; Sullivan, F
Abstract : OBJECTIVE--To identify reasons why some children receive more out of hours visits than most. DESIGN--A one year prospective study to identify the study group. This was followed by a case-control study involving a record search and personal interviews. SETTING--One three doctor urban general practice in West Lothian with 4812 patients. SUBJECTS--40 children aged under 10 years identified as high users of the out of hours service (more than two visits a year) and 40 age and sex matched controls. MAIN OUTCOME MEASURES--Numbers of visits; social factors such as lone motherhood, low educational attainment; score for management response to clinical vignette. RESULTS--147/756 (19%) out of hours visits in the study year were to children aged under 10 years; 109 (74%) to 41 children (6%). Problems seen were mainly minor, and little active management was required. Family and social factors which were significantly more common for the cases than for the controls included a lone mother (15 v 4), low educational attainment by the mother (25 v 14), receipt of income support (22 v 7), and non-ownership of the home (45 v 22) or a car (19 v 9). Mothers of the cases were more likely to choose to contact a doctor when presented with vignettes describing common childhood illnesses (median score for 16 vignettes 16.5 for cases v 14.5 for controls, Wilcoxon signed rank test, p = 0.01). CONCLUSIONS--Children seen more frequently than expected out of hours came from more socially disadvantaged families and their mothers were more likely to seek medical advice about minor childhood illness. Maternal education, to promote confidence in managing minor illness, may reduce their use of the out of hours service.